Partial volume correction for PET quantification and its impact on brain network in Alzheimer's disease. Issue 1 (December 2017) - Yang, Jiarui; Hu, Chenhui; Guo, Ning; Dutta, Joyita; Vaina, Lucia; Johnson, Keith; Sepulcre, Jorge; Fakhri, Georges; Li, Quanzheng
Abstract Amyloid positron emission tomography (PET) imaging is a valuable tool for research and diagnosis in Alzheimer's disease (AD). Partial volume effects caused by the limited spatial resolution of PET scanners degrades the quantitative accuracy of PET image. In this study, we have applied a method to evaluate the impact of a joint-entropy based partial volume correction (PVC) technique on brain networks learned from a clinical dataset of AV-45 PET image and compare network properties of both uncorrected and corrected image-based brain networks. We also analyzed the region-wise SUVRs of both uncorrected and corrected images. We further performed classification tests on different groups using the same set of algorithms with same parameter settings. PVC has sometimes been avoided due to increased noise sensitivity in image registration and segmentation, however, our results indicate that appropriate PVC may enhance the brain network structure analysis for AD progression and improve classification performance.